The Effect of Variable Oxygen Impurities on Microbial Activity in Conditions Resembling Geological Storage Sites. (July 2017) - Morgan, Hayden; Large, David; Bateman, Keith; Hanstock, David; Gregory, Simon
Abstract: Current specifications on carbon dioxide (CO2 ) storage do not take into account the effect of oxygen (O2 ) present as an impurity, on storage site microbiology. Some microbiology related impacts related to the CCS process include the potential blockage of injection well, corrosion of pipes, oil souring and oil degradation. To investigate this, microcosm experiments were set up using the O2 concentrations of 0 ppm, 10 ppm, 100 ppm and atmospheric. Artificial groundwater and sandstone microcosms were inoculated with a mixed microbial community, incubated for 29 days and regularly sampled for gases produced and sampled at the end of the experiment to analyse the microbiology. Gas chromatography analysis of these microcosms showed no hydrogen sulphide (H2 S) production and a variable amount of CO2 production. Microbial analysis of the microcosms show that the microbial inoculum (including sulphate reducing bacteria) was able to survive/grow better in the microcosms with 10 ppm and below compared to the higher levels of O2 . The levels of CO2 for 100 ppm and atmospheric levels of O2 were similar indicating the introduction of 100 ppm of O2 could promote aerobic processes. This experiment has shown that small differences in O2 concentrations affects microbial communities relevant to geological storage sites which could cause operational issues. Further investigation is required to properly assess the effect of small O2 changes on H2 S production.